PENGEMBANGAN LKPD BERBASIS PBL MELATIH LITERASI SAINS SISWA SD PADA MATA PELAJARAN IPA MATERI PERUBAHAN WUJUD BENDA - Tamam, Abdulloh; Suryanti; Sudibyo, Elok (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research aims to develop PBL-based LKPD to train students' scientific literacy skills. The sample in this study consisted of 27 students in class V B of SD Negeri 147 Gresik. Data analysis in this development research includes validity, practicality and effectiveness. The research results showed that the validity of the PBL model-based LKPD in the media aspect obtained a percentage of 94%, material 91%, and assessment instruments 89%. The practicality of PBL-based LKPD in the implementation of learning in meeting 1, the percentage is 97% and meeting 2 100%, in small group trial student activities in meeting 1 97% and meeting 2 100%, in large group trial student activities in meeting 1 97% and meeting 2 100% , in the student response to the small group trial at meeting 1 8.78% and at meeting 2 98.89%, in the student response to the large group trial at meeting 1 96.95% and at meeting 2 100%. The effectiveness of the posttest results showed that 1 student was in the poor category and 26 students were in the very good category. There are significant differences between the SPSS and manual T tests. The N-gain test was obtained at 0.73441 with the criteria for high student literacy abilities. The conclusion of this research is that the development of PBL-based LKPD is valid, practical and effective for training elementary school students' scientific literacy in science subjects regarding changes in the shape of objects.